The Mechanical Properties of Recycled Coarse Aggregate Concrete with Lithium Slag. (31st December 2019) - Qin, Yongjun; Chen, Jiejing; Li, Zhenxing; Zhang, Yabin
Abstract : Using recycled coarse aggregate (RCA) to replace natural pebbles and using lithium slag (LS) from industrial waste to replace cement in order to improve the mechanical properties of concrete and solve environmental problems. In this study, the effects of different substitution rates of RCA (0, 30%, 50%, and 70%) and different LS contents (0, 10%, 15%, 20%, and 25%) on the mechanical properties of concrete were investigated. The main results indicate that when the substitution rate of RCA is 30% and the LS content is 20%, optimal cube compressive strength, axial compressive strength, and elastic modulus can be achieved, with an increase of 9.90%, 48.22%, and 9.94% respectively; when the substitution rate of RCA is 70% and the LS content is 20%, the splitting tensile strength and flexural strength can be improved by 9.90% and 48.22%, respectively. The morphology of RCA concrete specimens with LS was observed with a scanning electron microscope (SEM). Moreover, corrections were made to improve the relevant formula according to the differences between the measured intensity index and data converted from current specifications.